Generalized simulated annealing: Application to silicon clusters - Lemes, M. R.; Zacharias, C. R. [UNESP]; Dal Pino, A. (American Physical Society (APS), 1997)
We have compared the recently introduced generalized simulated annealing (GSA) with conventional simulated annealing (CSA). GSA was tested as a tool to obtain the ground-state geometry of molecules. We have used selected silicon clusters (Sin, n=4-7,10) as test cases. Total energies were calculated through tight-binding molecular dynamics. We have found that the replacement of Boltzmann statistics (CSA) by Tsallis's statistics (GSA) has the potential to speed up optimizations with no loss of accuracy. Next, we applied the GSA method to study the ground-state geometry of a 20-atom silicon cluster. We found an original geometry, apparently lower in energy than those previously described in the literature.